PREVALENCE OF SOIL-TRANSMITTED HELMINTHS AMONG PRIMARY SCHOOL CHILDREN IN YANA, BAUCHI STATE, NIGERIA - MANSUR, SADDIQA; ABUBAKAR, BASHIR MOHAMMED; HASSAN, ISMAIL; ALIYU, UMAR (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2020)
Soil-Transmitted Helminths (STH) infections in developing countries like Nigeria still pose serious public health problems. The present study, therefore aimed to assess the prevalence of STH infections among students at Yana, Shira Local Government Area, Bauchi State Nigeria, from two randomly selected primary schools. A total of one hundred thirty-two students participated in the study. Stool samples were collected using clean sample bottles and processed by a standard parasitological technique for microscopic detection of STH. Data were analyzed using Chi square in SPSS version 24. Among the 132 (87 male and 45 female) children participated, 57 (43.2%) and 75(56.8%) were within the age groups of 4–6 and 7–10 respectively among the two schools. Fifty (37.9%) of them were tested positive for STH parasites. Hookworm (24, 18.1%) was the most frequently detected STH parasite followed by A. lumbricoides (14, 10.6%), Trichuris trichiura (9, 6.8%) and Taenia spp (3, 2.3%). There was no significant difference (p > 0.05) in prevalence of different STHs infections in relation to age group and gender across schools. This study also identified ova and larvae of STHs parasites in the analyzed soil samples from the studied schools. The prevalence of STH parasitic infection among school age children in this study area is still unacceptably high. This must relate to poor hygienic condition in the study area such as poor water supply, poor hand washing material as well as poor sanitary conditions. Therefore, school-based deworming and school health programs should be integrated to reduce the prevalence of STHs infection among the school-age children in the study area.